The Effects of Activities Management According to the CPA Approach on Learning Achievement and Mathematics Representation on Fraction of Grade 3 Students at The Demonstration School of Valaya Alongkorn Rajabhat University under the Royal Patronage in Pathum Thani Province - Anupan, Akarapon; Areeraksakul Konglok, Sureerat; Khaninphasut, Purimpratch (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Mathematical thinking processes help people apply mathematical knowledge to solve various problems effectively, therefore mathematics education needs to be continually developed. The purposes of this research were to 1) study the relationship between mathematics learning achievement and mathematics representation of grade 3 students in the group learning with CPA approach and 2) compare the mathematics learning achievement and mathematics representation of grade 3 students between the group learning with CPA approach and the group learning with conventional mathematics learning activities. Methodology: Quasi-experimental research used 2 sample groups consisting of 60 grade 3 students of The Demonstration School of Valaya Alongkorn Rajabhat University under the Royal Patronage in Pathum Thani Province during the first semester of the academic year 2023. Two classrooms, each with 30 students, were obtained by cluster random sampling. The employed research instruments consisted of 1) mathematics learning management plans on Fractions by using activities management according to the CPA approach 2) mathematics learning management plans on Fractions by using conventional mathematics learning activities 3) a mathematics learning achievement test and 4) an evaluation form for mathematics representation. Statistics employed for data analysis were the mean, standard deviation, Pearson’s correlation coefficient, and MANOVA test. Results: found that 1) the relationship between mathematics learning achievement and mathematics representation of grade 3 students learning with the CPA approach has a positive relationship with high correlation (r= 0.667, p<.01) counterpart ability at the .01 level with the percentage of covariation is 44.489. and 2) Mathematics learning achievement and mathematics representation of grade 3 students learning with the CPA approach was significantly higher than the group learning by using conventional mathematics learning activities counterpart ability at the .05 level. Conclusion: Grade 3 students in the group that received mathematics learning activities according to the CPA approach had higher academic achievement and mathematics presentation than the group that received normal learning activities because the CPA approach emphasizes that students learn on their own in a step-by-step manner through mathematics activities, starting with creating ideas using concrete materials. Train students to record their ideas as drawings. and convert concepts from drawings into text or mathematical symbols.